EVALUATION OF FUNGICIDES AND HERBICIDES AGAINST THE ROOT ROT OF OKRA - I. B. KAPADIYA; L. F. AKBARI; M. R. SIDDHAPARA; S. V. UNDHAD (The Bioscan, 2013)
Okra (Abelmoschus esculentus L.) is an important vegetable crop, severely attacked by root rot (Fusarium solani) in Junagadh district, Gujarat state (India). Therefore affords were made to screen the different systemic, contact and combination of fungicides and herbicides in vitro condition against test fungus. Among systemic fungicides, tebuconazole 25.9% EC gave cent per cent growth inhibition of test fungus followed by epoxyconazole 5% WP (92.69%) whereas contact fungicides, copper hydroxide 77% WP and thiram 75% WP were found effective and gave 91.94 and 78.04 per cent growth inhibition of test fungus. The combination of fungicides cymoxanil 8% WP + mancozeb 64% WP, metiram 55% WG + pyraclostrobin 5% WG and carbendazim 12% WP + mancozeb 63% WP gave cent per cent growth inhibition of test fungus. While in herbicides, oxadiargyl was proved to be most effective and gave cent per cent growth inhibition of test fungus followed by quizalophop-pethyle with mean per cent inhibition of 94.72 per cent.